A Planarized Thermophotovoltaic Emitter With Idealized Selective Emission - Sze Ming Fu; Yan Kai Zhong; Ming Hsiang Tu; Bo Ruei Chen; Albert Lin (IEEE Photonics Journal, 2016)
Compared with conventional solar cells, thermophotovoltaics (TPV) can be more efficient and, thus, exceeds the detailed balance efficiency limit. In particular, the emitter of TPV is a critical design since it determines whether the thermalization loss can be reduced and whether the sub-band-gap radiation can be suppressed, as far as the photovoltaic (PV) process is concerned. In this paper, we propose a selective planar emitter composed of alternating ultrathin metal and dielectric layers. An aperiodic dielectric stacking is designed to tailor the emission spectrum by shaping the emission peak and by adjusting the emission wavelength. We show that the peak emission wavelength $(λ_{emission})$ is adjustable from $λ=1500\ \text{nm}$ to $λ=2500\ \text{nm}$ . Furthermore, the long-wavelength cutoff is very sharp for our proposed emitter structure, and the absorption is suppressed to 0.1 beyond the cutoff. The preliminary experiment is also conducted to fulfill the concept of a fully planar ultrathin refractory metal emitter design, and the result is similar to the calculated ones. We believe that the planar thermal emitter based on ultrathin metals and aperiodic dielectric stacking is very promising for future thermal emission applications since it requires no lithography and etching, provides strong peak emission power, and possesses wide wavelength scalability.